Menumbuhkan Konsep Diri Positif melalui Konseling Kelompok Realitas di Lembaga Pembinaan Khusus Anak di Kota Kupang - Merita Florawati Naisanu; Maria Natalia Loban; Erly Oviane Malelak; Joris Taneo; Frengky Yohanes (I-Com: Indonesian Community Journal, 2024)
Adolescents who are involved in criminal activities and are required to serve time in juvenile correctional institutions may experience negative changes in their views of themselves. Limited opportunities to develop and adapt like individuals in general can cause teenagers serving prison terms to feel marginalized by their surrounding environment, resulting in the formation of a self-concept that tends to be negative. Reality group counseling with the WDEP approach (Want, Doing and Direction, Self Evaluation, Planning) system can be used as an alternative to foster a positive self-concept, namely by providing understanding to individuals so that individuals are able to assess themselves positively. The result of reality group counseling is that participants gain insight into forming a positive self-concept that can be developed in their lives as inmates at LPKA in Kupang City. The achievement of the objectives of this activity can be seen in the participants' ability to use a practical counseling approach and change their self-concept perspective in a more positive direction. Keywords: Self Concept 1 ; Group Counseling2; Reality3 ;